Pengaruh Kualitas Layanan dan Pengalaman Konsumen Terhadap Loyalitas Destinasi Jamaah Umroh - Sentoso, Diah Harjaningtyas; Andajani, Erna; Rahayu, Siti (Akutansi Bisnis & Manajemen ( ABM ), 2021)
the purpose of this study is to determine the effect of destination loyalty modeling that embody of service quality on destination image, destination image on destination loyalty, destination image on destination satisfaction, consumer experience on destination satisfaction, consumer experience on destination loyalty, destination satisfaction on destination loyalty. In this study, the type of research that will be used in this thesis is a type of quantitative research, where this research will collect data from questionnaires targeting Indonesian pilgrims in Medina and Mecca. The methodology of this research study will be processed with SEM AMOS. The research results that service quality influences destination loyalty, destination image influences destination loyalty, destination image influences destination satisfaction, consumer experience influences destination satisfaction, consumer experience influences destination loyalty, destination satisfaction influences destination loyalty.